Suppression of hypothalamic-pituitary-adrenal axis by acute heroin challenge in rats during acute and chronic withdrawal from chronic heroin administration - Zhou, Yan (2013)
It is known that heroin dependence and withdrawal are associated with changes in the hypothalamic-pituitary-adrenal (HPA) axis. The objective of these studies in rats was to systematically investigate the level of HPA activity and response to a heroin challenge at two time points during heroin withdrawal, and to characterize the expression of associated stress-related genes 30 minutes after each heroin challenge. Rats received chronic (10-day) intermittent escalating-dose heroin administration (3×2.5 mg/kg/day on day 1; 3×20 mg/kg/day by day 10). Hormonal and neurochemical assessments were performed in acute (12 hours after last heroin injection) and chronic (10 days after the last injection) withdrawal. Both plasma ACTH and corticosterone levels were elevated during acute withdrawal, and heroin challenge at 20 mg/kg (the last dose of chronic escalation) at this time point attenuated this HPA hyperactivity. During chronic withdrawal, HPA hormonal levels returned to baseline, but heroin challenge at 5 mg/kg decreased ACTH levels. In contrast, this dose of heroin challenge stimulated the HPA axis in heroin naïve rats. In the anterior pituitary, pro-opiomelanocortin (POMC) mRNA levels were increased during acute withdrawal and retuned to control levels after chronic withdrawal. In the medial hypothalamus, however, the POMC mRNA levels were decreased during acute withdrawal, and increased after chronic withdrawal. Our results suggest a long-lasting change in HPA abnormal responsivity during chronic heroin withdrawal.